SKRINING KEJADIAN ANDROPAUSE PADA OBESITAS SENTRAL PRIA DI WILAYAH KERJA PUSKESMAS KARYA MULIA KECAMATAN PONTIANAK KOTA - ., Andari Putri Wardhani (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Andropause is a symptom and disease complaint that is associatedwith the decrease in the male hormone testosterone. WHO reported that inseveral countries, male hormone testosterone, decreases by 10% in everydecade by the age of 30. There are many progressive risk factors onandropause, they are central obesity, age, and medical history.Objective: This research is aimed to see the correlation between the centralobesity by using abdominal circumference measurement and andropause byscreening throughs using ADAM questionnaires on adult males by the age above40 in Puskesmas Karya Mulia Pontianak Kota.Methods: This reserach uses analytical method with cross-sectional researchdesign which is done on 95 respondents. Data is prossessed by Chi-square testwith p<0.05.Results: Total subject of research is 95 respondents, 46 respondents (48.4%)experienced andropause and the other 49 respondents (51.6%) do notexperience the andropause itself. Based on the analytical result, it comes with pvalue which is meant on the correlation between male central obesity andandropause.Conclusion: There is a correlation between central obesity on adult male andandropause in Puskesmas Karya Mulia Working Area Kecamatan PontianakKota.Keywords: Andropause, Central Obesity, Age, MaleDescriptions:1. Medical Education Study Program, Medical Faculty, Tanjungpura University,Pontianak, West Borneo,2. Department of Internist, Kharitas Bhakti Hospital, Pontianak, West Borneo,3. Department of Public Health, Medical Education Study Program, Medical FacultyTanjungpura University, Pontianak, West Borneo.